On the causal links between FDI and growth in developing countries - Henrik Hansen; John Rand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
We analyse the Granger causal relationships between foreign direct investment (FDI) and GDP in a sample of 31 developing countries covering 31 years. Using estimators for heterogeneous panel data we find bi-directional causality between the FDI-to-GDP ratio and the level of GDP. FDI has a lasting impact on GDP, while GDP has no longrun impact on the FDI-to-GDP ratio. In that sense FDI causes growth. Furthermore, in a model for GDP and FDI as a fraction of gross capital formation (GCF) we also find long-run effects from FDI to GDP. This finding may be interpreted as evidence in favour of the hypotheses that FDI has an impact on GDP via knowledge transfers and adoption of new technology.
Keywords: O4; F21; C33; 330; economic growth; foreign direct investment; Granger causality; panel data; Wirtschaftswachstum; Direktinvestition; Sozialprodukt; Kausalanalyse; Entwicklungsländer